Creating New Humans: Tracking the Path of Graduates from the Management Study Program at Paramadina University - Agnes Anvista Putri; Garnis Aulia; Dewi Kurniaty (SEAN Institute, 2024)
This study investigates the perceptions of stakeholders regarding the Management Study Program at Paramadina University, emphasizing the importance of tracer studies for curriculum evaluation and alignment with industry needs. The research utilizes a descriptive quantitative method, collecting data from alumni through surveys. Results show that most graduates secure employment quickly, particularly in the private sector, with a focus on Human Resources and Marketing. Graduates generally feel confident in their competencies, especially in ethics, communication, and information technology, although there is room for improvement in certain areas. The findings highlight the need for continuous curriculum enhancement to better prepare students for the evolving job market and to maintain the competitiveness of graduates.